Enablers and barriers of internationalization in e-commerce : Finnish retail SMEs in focus - Wendelin, Olli (My University, 2020)
In the past years, e-commerce has been growing quickly at the same time when economic growth in developed economies has been modest. Moreover, e-commerce is increasingly inter- national. This study focuses on describing and analyzing the process of internationalization in e-commerce with Finnish retail SMEs in focus. The main research question is to find out why Finnish e-commerce companies struggle in the competition with their Swedish counterparts? The sub-objectives of the study are to find out what are the firm-specific determinants that influence the internationalization of a certain e-commerce firm, and on the other hand, what are the enablers and barriers of internationalization for Finnish e-commerce firms. The study begins with building a preliminary theoretical framework based on previous literature on the topic, including an overview on e-commerce companies, internationalization theory and presenting of previous studies on enablers and barriers of internationalization. The empirical research was conducted by six semi-structured expert interviews based on the theo- retical framework. The interviewees were chosen by their expertise and experiences in e-com- merce and internationalization. However, as the research was explorative by nature, the re- searcher emphasized on finding surprising new themes emerging from the data. The findings of the study support the existing theory to a large extent but also offers new interesting information particularly on the enablers and barriers of internationalization of Finn- ish e-commerce firms. The study underlines the importance of social media platforms and mar- keting tools that create an efficient channel for global brand marketing and internationalization in e-commerce. On the other hand, the study suggests that there are basically no risk-investors nor banks keen on investing in growing e-commerce businesses in Finland. On the contrary in Sweden, various successful e-commerce business cases have lured investors and created buzz around the industry. To conclude, the empirical findings offer interesting insight to the main research question of the study and well as to the research field of internationalization in e-commerce. However, as only a half a dozen interviews were conducted, the findings remain superficial and larger empirical research is required in order to make more generalizable conclusions.

Verkkokauppa on kasvanut viime vuosina nopeasti samaan aikaan, kun kehittyneiden talouksien talouskasvu on ollut vaatimatonta. Lisäksi verkkokauppa on yhä kansainväli-sempää. Tämä tutkimus keskittyy kuvaamaan ja analysoimaan verkkokaupan kansainvä-listymisprosessia suomalaisen kaupan alan pk-yrityksen näkökulmasta. Tutkimuksen ta-voitteena on selvittää miksi suomalaiset verkkokauppayritykset eivät pärjää kilpailuissa ruotsalaisten yritysten kanssa? Tutkimuksen alatavoitteet pureutuvat yrityskohtaisiin teki-jöihin, jotka vaikuttavat verkkokauppayrityksen kansainvälistymiseen, ja toisaalta kysy-mykseen mitkä ovat suomalaisten verkkokauppayritysten kansainvälistymisen mahdollis-tavat ja estävät tekijät. Tutkimus alkaa aikaisempaan kirjallisuuteen perustuvan teoreettisen kehyksen raken-tamisella, joka sisältää yleiskatsauksen verkkokauppayrityksistä, kansainvälistymisteorias-ta ja kansainvälistymisen mahdollistavista ja estävistä tekijöistä. Tutkimuksen empiirinen osa suoritettiin kuudella puolistrukturoidulla asiantuntijahaastattelulla, jotka perustuivat tutkimuksen teoreettiselle viitekehykselle. Haastateltavat valittiin verkkokaupassa kan-sainvälistymisen kokemuksien perusteella ja asiantuntemuksen perusteella. Tutkimus oli luonteeltaan tutkiva ja tutkija halusi löytää uutta ja yllättävää tietoa käsiteltävästä ilmiöstä. Tutkimuksen löydökset tukevat suurelta osin olemassa olevaa teoriaa, mutta ne tuot-tivat myös uutta mielenkiintoista tietoa etenkin suomalaisten verkkokauppayritysten kan-sainvälistymisen mahdollistavista ja estävistä tekijöistä. Löydökset korostavat sosiaalisen median alustojen ja markkinointityökalujen merkitystä, luoden tehokkaan kanavan glo-baaliin brändimarkkinointiin ja kansainvälistymiseen verkkokaupassa. Toisaalta tutki-muksen mukaan Suomessa ei käytännössä ole riskisijoittajia eikä pankkeja, jotka haluai-sivat investoida kasvaviin verkkokaupan alan yrityksiin, kun taas Ruotsissa useat menes-tyneet verkkokaupat ovat houkuttaneet sijoittajia ja luoneet kiinnostusta koko toimialan ympärille. Yhteenvetona voidaan todeta, että empiiriset havainnot tarjoavat mielenkiintoisia vastauksia tutkimuksen pääkysymykseen sekä laajemmin verkkokaupan kansainvälisty-mistutkimukseen. Täytyy kuitenkin muistaa, että tutkimus toteutettiin vain kuuden asian-tuntijahaastattelun avulla, joten havainnot säilyvät pintapuolisena ja tarvitaan laajempaa empiiristä tutkimusta yleisemmin arvioitavissa olevien päätelmien tekemiseksi.
Keywords: E-commerce, internationalization, enablers, barriers, Finnish, SME